Spiritual Vibrations and Vedic Philosophy as Foundations of Balinese Culture and Global Appeal: The Sakala-Niskala as Parā Vidyā-Aparā Vidyā Paradigm - Ketut Donder; I Ketut Sudarsana; I Dewa Gede Rat Dwiyana Putra; Prasanthy Devi Maheswari (Universitas Udayana, 2025)
This article aims to explain how the Balinese sakala-niskala (visible-invisible) as Parā Vidyā-Aparā Vidyā paradigm produces the spiritual vibrations that form the foundation of Bali's sustained international appeal. Utilizing a qualitative methodology, this research synthesizes classical Advaita Vedanta and modern Vibration Theory. The data includes ethnographic observations and systematic interviews with key religious and cultural informants. Symbolic Interactionism is employed to interpret how these subtle energies are perceived and communicated by global visitors. Findings reveal that the concept of sakala-niskala is operationalized through Balinese rituals, which generate a dynamic vibrational field that influences both the environment and individual consciousness. The novelty lies in demonstrating that Bali’s sustained global appeal is directly attributable to the systematic maintenance of this vibrational ecology. This study contributes a new analytical model to spiritual geography and provides actionable insights for policymakers on establishing sustainable tourism governance that prioritizes the preservation of these unique vibrations.